2011
DOI: 10.1002/pc.21117
|View full text |Cite
|
Sign up to set email alerts
|

Study on the viscosity of polypropylene composites filled with different size and size distribution CaCO3

Abstract: Two kinds of different size calcium carbonates are blended and filled into polypropylene in 30 wt%. The melting viscosity of PP composites samples is measured by capillary extrusion rheometer at 2308C. The results show that the melt viscosity of PP composites evidently decreased when that was filled with the blending 325 and 1,500 mesh CaCO 3 and the 1,500 mesh proportion in fillers was from 20 to 60 wt%. The viscosity in the low shear velocity decreased more than that in the high shear velocity. The shear vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…For example, rheological percolation was observed when NFs concentration exceeded a critical value. As a result, the viscoelastic HFPNCs melts showed solid-like behaviour owing to the effect of filler–filler and filler–chains networks [2, 10-12].…”
Section: Introductionmentioning
confidence: 99%
“…For example, rheological percolation was observed when NFs concentration exceeded a critical value. As a result, the viscoelastic HFPNCs melts showed solid-like behaviour owing to the effect of filler–filler and filler–chains networks [2, 10-12].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical properties of the composites are closely related to their macroscopic defect morphology, the particle size distribution of the filler, and the contact state of the microscopic interfaces between the fillers 30–33 . The results show that the thermoplastics filled with CaCO 3 with different particle size distributions have lower melting crystallization temperature and lower melting viscosity than the composites filled with a single particle size, which improves the machining and mechanical properties of the composites significantly 22,34–36 . In a study of mica as filler‐reinforced polypropylene, Busigin et al 37 noted that the modulus of the composite was related to the aspect ratio of the mica, and the strength was influenced the most by the size or scale diameter of the mica.…”
Section: Introductionmentioning
confidence: 98%
“…[30][31][32][33] The results show that the thermoplastics filled with CaCO 3 with different particle size distributions have lower melting crystallization temperature and lower melting viscosity than the composites filled with a single particle size, which improves the machining and mechanical properties of the composites significantly. 22,[34][35][36] In a study of mica as filler-reinforced polypropylene, Busigin et al 37 noted that the modulus of the composite was related to the aspect ratio of the mica, and the strength was influenced the most by the size or scale diameter of the mica. However, in the field of high-filled thermosetting resin composites, there is a lack of corresponding research on CaCO 3 gradation, leading to the question of how CaCO 3 gradation affects the material properties is long puzzled.…”
Section: Introductionmentioning
confidence: 99%
“…The use of mineral fillers can provide to the membrane an increase in rigidness, an enhancement of the hydrophilic surface characteristic and also can affect to the final porous morphology of the membranes, as most of the fillers have some nucleating ability in the crystallization processes of polyolefins. [7][8][9][10][11][12] Caihong et al [13] used magnesium sulfate whiskers as filler and showed that with increasing whiskers content the porosity of the stretched microporous membranes decreased, whereas the Gurley value showed an increase in values, they also showed that the introduction of MgSO 4 up to 10 wt.% did not induce pronounced changes in the pore structure and air permeability properties of the stretched microporous membranes.…”
Section: Introductionmentioning
confidence: 99%